Multiple sclerosis-associated CD226 variant disrupts vitamin D-induced type I Treg differentiation by impairing LFA-1 activation - Saniya Kari; Aymeline Debonlier; Thibault Angles; Beatriz Chaves; Charles Grosjean; Florence Bucciarelli; Valérie Duplan-Eche; Lucie Nozeran; Jessica Lavery; Elena Morandi; Beatrice Pignolet; Max Mimpen; et al. (Journal of Clinical Investigation, 2026)
Multiple sclerosis (MS) is a complex inflammatory disease of the CNS resulting from an intricate interplay between genetic predisposition and environmental factors. Vitamin D (VD) deficiency is one of the established risk factors for MS. CD46 costimulation of CD4 + T cells induces a switch from Th1 to type I regulatory cells (Tr1), characterized by increased IL-10 production. This switch is impaired in MS T cells but can be restored by VD, which also strongly promotes expression of CD226 on CD46-activated T cells. The rs763361 polymorphism in the CD226 gene, resulting in a non-synonymous Gly307Ser variant, is associated with increased risk for MS. Herein, we show that expression of this CD226 risk allele disrupts the ability of CD46-activated T cells to operate the IFNγ/IL-10 switch upon VD exposure. Mechanistically, the risk variant impairs activation of the integrin LFA-1, which promotes the Tr1 phenotype. LFA-1-mediated Tr1 differentiation is also impaired in MS T cells expressing the CD226 risk allele upon CD46 and VD stimulation. Our study unveils how, in the context of MS susceptibility, a genetic polymorphism and an environmental factor act in concert to control the differentiation of Tr1 cells.